Analysis, Design and Implementation of a Non‐isolated Switched Inductor/Capacitor Converter with Low Voltage Spikes. Issue 7 (18th May 2021) - Jiang, Wei; Zhang, Shaoru; Du, Xiuju; Yang, Wenxiu; Luo, Fang Lin
Abstract : In order to take the advantage of boost capability and filtering characteristics of the switched inductor/capacitor, a non‐isolated switched inductor/capacitor (NSI/C) converter is proposed. The topological structure of the non‐isolated switched inductor/capacitor converter is analyzed in detail, and the DC steady‐state model is established in continuous conduction mode (CCM). The voltage gain of the converter and the stress of the switch in the converter are theoretically deduced and compared with the existing converters; the parameter design of the inductance and capacitance is calculated. The simulation model was built in MATLAB/Simulink, and the correctness of the theoretical calculation for the proposed converter was verified by simulation results. Finally, the experimental prototypes of the proposed converter and the non‐isolated high step‐up (NHS) converter were built. Through the comparison of experimental results, the feasibility and validity of the design scheme for the proposed converter are verified. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.